KOMA THEATER’S MARKETING THROUGH SOCIAL MEDIA CASE STUDY: 'GEMINTANG' SHOW - Danastri, Dhiaz; Dwirizky, Putri; Kurniawan, Tonie (Dinasti International Journal of Digital Business Management, 2020)
For around 41 years, Theater Koma did not stop working. Continued to produce until its name is increasingly known, then holds a special place in the hearts of its fans. It's not an easy thing to maintain a theater community which in Indonesia is not yet popular. As the times changed, slowly but surely, Theater Koma's audience entered a period of regeneration. Performing arts production requires proper marketing techniques so the show could be accepted by the target community. Social media is a massive growth area for online marketers and one of which has potential to offer highly targeted advertising to specialized social groups. The transition of Theater Koma's marketing technique from offline to the digital world by utilizing social media needs to be developed because it is important in effort to regenerate the audience. This scientific was made written by conducting field observations during production process of the “Gemintang” show from mid-April 2018 to July 15 2018. This research aims to let us know the marketing techniques which have been applied to production of “Gemintang” show. This research concludes that awareness of the need for the existence of an art group is not only proven by work productivity itself, but how the work could be recognized and accepted by various segments of society which current entered the digital era.